No cumulative effect of 10 years of elevated [CO2] on perennial plant biomass components in the Mojave Desert. (3rd April 2013) - Newingham, Beth A.; Vanier, Cheryl H.; Charlet, Therese N.; Ogle, Kiona; Smith, Stanley D.; Nowak, Robert S.
Abstract Elevated atmospheric CO2 concentrations ([CO2]) generally increase primary production of terrestrial ecosystems. Production responses to elevated [CO2] may be particularly large in deserts, but information on their long‐term response is unknown. We evaluated the cumulative effects of elevated [CO2] on primary production at the Nevada Desert FACE (free‐air carbon dioxide enrichment) Facility. Aboveground and belowground perennial plant biomass was harvested in an intact Mojave Desert ecosystem at the end of a 10‐year elevated [CO2] experiment. We measured community standing biomass, biomass allocation, canopy cover, leaf area index (LAI), carbon and nitrogen content, and isotopic composition of plant tissues for five to eight dominant species. We provide the first long‐term results of elevated [CO2] on biomass components of a desert ecosystem and offer information on understudied Mojave Desert species. In contrast to initial expectations, 10 years of elevated [CO2] had no significant effect on standing biomass, biomass allocation, canopy cover, and C : N ratios of above‐ and belowground components. However, elevated [CO2] increased short‐term responses, including leaf water‐use efficiency (WUE) as measured by carbon isotope discrimination and increased plot‐level LAI. Standing biomass, biomass allocation, canopy cover, and C : N ratios of above‐ and belowground pools significantly differed among dominant species, but responses to elevated [CO2] did not vary among species, photosynthetic pathway (C3 vs. C4), or growth form (drought‐deciduous shrub vs. evergreen shrub vs. grass). Thus, even though previous and current results occasionally show increased leaf‐level photosynthetic rates, WUE, LAI, and plant growth under elevated [CO2] during the 10‐year experiment, most responses were in wet years and did not lead to sustained increases in community biomass. We presume that the lack of sustained biomass responses to elevated [CO2] is explained by inter‐annual differences in water availability. Therefore, the high frequency of low precipitation years may constrain cumulative biomass responses to elevated [CO2] in desert environments.